Review on Mechanical Support and Cell-Based Therapies for the Prevention and Recovery of the Failed Fontan-Kreutzer Circulation - Ferrari, Margaret R.; Di Maria, Michael V.; Jacot, Jeffrey G. (Frontiers in Pediatrics, 2021)
Though the current staged surgical strategy for palliation of single ventricle heart disease, culminating in a Fontan circulation, has increased short-term survival, mounting evidence has shown that the single ventricle, especially a morphologic right ventricle (RV), is inadequate for long-term circulatory support. In addition to high rates of ventricular failure, high central venous pressures (CVP) lead to liver fibrosis or cirrhosis, lymphatic dysfunction, kidney failure, and other comorbidities. In this review, we discuss the complications seen with Fontan physiology, including causes of ventricular and multi-organ failure. We then evaluate the clinical use, results, and limitations of long-term mechanical assist devices intended to reduce RV work and high CVP, as well as biological therapies for failed Fontan circulations. Finally, we discuss experimental tissue engineering solutions designed to prevent Fontan circulation failure and evaluate knowledge gaps and needed technology development to realize a more robust single ventricle therapy.